Feedback Linearization and Maximum Torque per Ampere Control Methods of Cup Rotor Permanent-Magnet Doubly Fed Machine - Jianning Shi; Chaoying Xia (Energies, 2021)
This paper establishes the state-space model of the cup rotor permanent-magnet doubly fed machine in the synchronous reference frame. The feedback-linearization control method is used to realize the decoupling control of flux and torque. Then, the upper and lower load torque boundaries are solved. Furthermore, to minimize the stator current magnitude of the control machine under a certain torque, the maximum torque per ampere (MTPA) control is derived. Finally, simulation results demonstrate the good decoupling performance of the feedback-linearization control method and the correctness of the load torque boundaries. In addition, the effectiveness and robustness of the proposed control methods are also demonstrated.